Strategic Agility and Organizational Resilience: How Adaptive Strategies Drive Business Continuity in Dynamic Environments - Artis; Jalaluddin, T.; Primasari, Niken Savitri; Coryanata, Isma (Malaqbi Publisher, 2026)
This study examines the role of strategic agility in enhancing organizational resilience and ensuring business continuity within dynamic and uncertain environments. Drawing on dynamic capability theory, the research investigates how adaptive strategies—such as rapid decision-making, resource flexibility, and proactive sensing—enable organizations to withstand disruptions and maintain operations. Using a quantitative research design with structural equation modeling (SEM), the findings reveal that strategic agility exerts a significant positive effect on both organizational resilience and business continuity. Additionally, organizational resilience is shown to strongly influence business continuity and mediates the relationship between strategic agility and continuity outcomes. These results demonstrate that agility enables organizations to anticipate change, while resilience operationalizes these capabilities to absorb shocks and recover effectively. The model exhibits strong explanatory power and robust validity, reinforcing the interdependence between agility and resilience as essential strategic capabilities. This study contributes to the literature by offering an integrated framework for understanding how adaptive strategies enhance organizational stability and performance in volatile contexts. Practical implications are also provided to guide leaders in embedding agility and resilience into strategic planning and operational processes.